The Role of Public Relations in Maintaining Good Relations Between Campus Internal Organizations at UIN SU Medan - Ima Sania Nur Rizky; Nur Khairunisa Putri; Frisan Malik; Mahiruddin Nasution (Journal of Global Islamic Economic Studies, 2024)
The role of Public Relations in maintaining good relations between internal campus organizations is an important aspect in creating synergy and harmonization within the North Sumatra State Islamic University (UINSU). This research aims to explore the strategic role of Public Relations in maintaining effective communication, identifying obstacles faced, and proposing strategies for managing relations between internal campus organizations. Through a qualitative descriptive approach, this research reveals that Public Relations plays a role as a liaison and mediator in managing communication between the Student Executive Board (BEM), Department Student Association (HMJ), and Student Activity Unit (UKM). The main obstacles faced include a lack of involvement from related parties, miscommunication, and differences in interests between organizations. To overcome these obstacles, effective strategies include strengthening communication systems, implementing a participatory approach, and optimizing internal campus media. It is hoped that these findings can become a reference for higher education institutions in developing the role of Public Relations to strengthen synergy between internal organizations.